The Prevalence of the EML4-ALK Fusion Gene in Cytology Specimens from Patients with Lung Adenocarcinoma - Didik S. Heriyanto; Ika Trisnawati; Evan G. Kumara; Vincent Laiman; Fara S. Yuliani; Auliya S. B. Sumpono; Rita Cempaka; Marcellus; Eko Budiono (Pulmonary Medicine)
Background. Under the National Comprehensive Cancer Network (NCCN) guidelines for non-small-cell lung carcinoma (NSCLC), anaplastic lymphoma kinase (ALK) gene rearrangement is required to be assessed. However, data showing the prevalence of the ALK rearrangement is still deficient and is not yet available in Indonesia. This study used direct smear preparation from transthoracic needle specimens that are minimally invasive. The main objective of the study is to identify the prevalence of the ALK fusion rearrangement gene in cytological specimens. Materials and Methods. A total of 35 direct smear preparations diagnosed as lung adenocarcinoma and EGFR mutation negative were involved in this study. The samples were taken between 2017 and 2019. These samples were examined for EML4-ALK fusion rearrangement gene using qRT-PCR. The EML4-ALK rearrangement status was determined by qRT-PCR with high-resolution melting (HRM) analysis. Results. A total of 28 (80%) samples were from males, and 7 samples were from females. Seven (20% 95% CI: 8.4%-36.9%) samples were EML4-ALK rearrangement positive. The average age of the patients was 63.5 years old. The most common sites of metastasis in this study were pleural cavity, bone, liver, and CNS. Conclusions. qRT-PCR successfully identified EML4-ALK fusion rearrangement in direct smear preparations of lung adenocarcinoma. Direct smear samples can be used for EML4-ALK rearrangement detection using qRT-PCR. The EML4-ALK rearrangement gene has high prevalence in selected lung adenocarcinoma and EGFR mutation-negative populations. ALK inhibitors in lung cancer can be openly considered for use in Indonesian patients to improve the outcome of this subset of patients.